Al-Biruni's Contribution To The Development Of Qibla Determination Methods: Historical Analysis And Scientific Relevance - Abdul Kohar (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Abu Raihan Muhammad bin Ahmad Al-Biruni, a prominent Muslim scholar born in 973 CE, made important contributions to the development of a more accurate method of Qibla direction determination. This Research aims to explore Al-Biruni's contribution to overcoming the limitations of traditional methods that lack precision by developing an innovative approach that combines astronomical observations and sophisticated mathematical calculations. By utilizing the positions of celestial bodies, such as the stars Canopus and Polaris, as well as the Sun's direction during the summer and winter solstices, Al-Biruni achieved a more accurate determination of Qibla. The research methodology uses a qualitative approach that includes an analysis of Al-Biruni's monumental work, Al-Qanun al-Mas'udi, especially book 5, section 5, which contains detailed calculations using spherical trigonometry and celestial sphere diagrams, as well as the application of sine and cosine rules in the process of calculating the Qibla Direction. The research findings show that Al-Biruni's method, which utilizes the positions of celestial bodies and spherical astronomical calculations, can produce a Qibla direction determination with a level of accuracy comparable to that of modern techniques. The originality of this approach lies in its systematic integration of astronomy and mathematics, which not only increases the accuracy of Qibla direction determination but also provides a basis for the development of contemporary scientific methods. The results of this research confirm the relevance and significance of Al-Biruni's method in bridging spiritual needs and scientific progress.